Police respond to terrorism: case studies from India, France, Belgium, and England - Heyer, Garth den (Springer, 2023)
Chapter 1 – Introduction -- Chapter 2 – The theory of the police response to terrorism -- chapter 3 – The 2008 terrorist attacks in Mumbai -- Chapter 4 – The threat of terrorism in Europe -- Chapter 5 – The 2015 terrorist attacks in Paris -- Chapter 6 – The 2016 terrorist attacks in Brussels -- Chapter 7 – The 2017 terrorist attacks in Manchester -- Chapter 8 – Analysis of the police response to the terrorist attacks in Mumbai, Paris, Brussels and Manchester -- Chapter 9 – How can the police response to terrorist attacks be improved? -- Chapter 10 – Conclusion.